Distal Aortic Failure Following the Frozen Elephant Trunk Procedure for Aortic Dissection - Berger, Tim; Graap, Miriam; Rylski, Bartosz; Fagu, Albi; Gottardi, Roman; Walter, Tim; Discher, Philipp; Hagar, Muhammad Taha; Kondov, Stoyan; Czerny, Martin; Kreibich, Maximilian (Frontiers in Cardiovascular Medicine, 2022)
Background Aim of this study was to report and to identify risk factors for distal aortic failure following aortic arch replacement via the frozen elephant trunk (FET) procedure. Methods One hundred sixty-eight consecutive patients underwent the FET procedure for acute and chronic aortic dissection. Our cohort was divided into patients with and without distal aortic failure. Distal aortic failure was defined as: (I) distal aortic reintervention, (II) aortic diameter dilatation to ≥6 cm or >5 mm growth within 6 months, (III) development of a distal stent-graft-induced new entry (dSINE) and/or (IV) aortic-related death. Preoperative, intraoperative, postoperative and aortic morphological data were analysed. Results Distal aortic failure occurred in 88 (47.3%) patients. Forty-six (24.7%) required a distal reintervention, aortic diameter dilatation was observed in 9 (4.8%) patients, a dSINE occurred in 22 (11.8%) patients and 11 (6.4%) suffered an aortic-related death. We found no difference in the number of communications between true and false lumen (p=0.25) but there were significantly more communications between Ishimaru zone 6-8 in the distal aortic failure group (p=0.01). The volume of the thoracic descending aorta measured preoperatively and postoperatively within 36 months afterwards was significantly larger in patients suffering distal aortic failure (p<0.001; p=0.011). Acute aortic dissection (SHR 2.111; p=0.007), preoperative maximum descending aortic diameter (SHR 1.029; p=0.018) and preoperative maximum aortic diameter at the level of the diaphragm (SHR 1.041; p=0.012) were identified as risk factors for distal aortic failure. Conclusions The incidence and risk of distal aortic failure following the FET procedure is high. Especially those patients with more acute and more extensive aortic dissections or larger preoperative descending aortic diameters carry a substantially higher risk of developing distal aortic failure. The prospective of the FET technique as a single-step treatment for aortic dissection seems low and follow-up in dedicated aortic centres is therefore paramount.